The Impact of Intangible Assets and Fair Value Measurement on Audit Fees: Empirical Evidence from Jordanian Banking Sector - Al Karaki, Sulieman Mohammed A.; Al-Thuneibat, Ali A. (Jordan Journal of Business Administration, 2022)
This study aims at providing evidence concerning the impact of intangible assets and fair value measurement at levels 1 and 2 on audit fees. A sample of 13 Jordanian commercial banks with 91 observations over the period from 2011 through 2017 was used. Descriptive statistics and regression analysis were used to analyze the data and test the hypotheses of the study. The findings of the study show that there is an insignificant impact for both intangible assets and fair valued assets measured at level 1 on audit fees. However, the results show that there is a significant impact of fair valued assets measured at level 2 on audit fees, a result which is consistent with a hypothesized scenario that a high level of uncertainty of estimation results in higher audit fees. The researchers recommend that more attention should be given by commercial banks and audit firms to fair value measurement before arrangements related to audit fees, taking into account that a high level of uncertainty of estimation of fair value results in a higher audit risk and therefore, higher audit fees.